Pipette-tip kapok fiber-based solid-phase extraction/in-situ derivatization for the rapid and green analysis of furfural compounds - Xiangyu Li; Qian Qin; Yanbo Luo; Yongqiang Pang; Jinchao Wei; Xingyi Jiang; Di Chen (Food Chemistry: X)
Furfural compounds, including 5-hydroxymethylfurfural, furfural, and 5-methylfurfural, are common in foods and pose health risks. This study presents a pipette-tip solid-phase extraction with in-situ derivatization (PT-KF-SPE/ISD) method for rapid analysis of furfural compounds in various food matrices. Utilizing natural kapok fiber as an efficient adsorbent, this method integrates extraction and derivatization into a single step via a simple pull-push operation. Derivatization with 2,4-dinitrophenylhydrazine increases the hydrophobicity and ultraviolet absorption of furfural compounds, enabling sensitive liquid chromatography-ultraviolet detection. The method shows good linearity, sensitivity, and reproducibility, with limits of detection in ranges of 3.9–6.0 ng/mL. Real sample analysis confirms its applicability in detecting furfural compounds in beverages and herbal products, offering a reliable and eco-friendly solution for food safety and quality control. Five greenness assessment metrics demonstrate the method's excellent environmental friendliness. This approach highlights the advantages of combining natural adsorbents with in-situ derivatization for efficient food analysis.